2018
DOI: 10.1063/pt.3.3816
|View full text |Cite
|
Sign up to set email alerts
|

Introductory physics labs: We can do better

Abstract: Research reveals that labs are more effective when their goal is to teach experimental practices rather than to reinforce classroom instruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(76 citation statements)
references
References 17 publications
1
69
0
1
Order By: Relevance
“…The list of activities associated with this practice has a great deal of overlap with the goals of a typical physics lab activity. This raises the possibility that CT may contribute something useful to the current debate over the usefulness of physics labs ( [13,14]). We will return to this topic later.…”
Section: Defining Computational Thinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…The list of activities associated with this practice has a great deal of overlap with the goals of a typical physics lab activity. This raises the possibility that CT may contribute something useful to the current debate over the usefulness of physics labs ( [13,14]). We will return to this topic later.…”
Section: Defining Computational Thinkingmentioning
confidence: 99%
“…It is not difficult to imagine similar activities for projectile motion or the "coffee filter" experiment where students model the mo-tion of a falling object with air drag. There is some debate now regarding the value of physics labs [13,14] and activities of this kind may provide a useful new direction for research, especially now that an increasing number of smartphones and tablets can record slow motion video at 240 frames per second. This is the same frame rate that many of excellent direct measurement videos from Peter Bohacek 1 were recorded [24].…”
Section: Thoughts For the Futurementioning
confidence: 99%
“…In a landmark study, the contributions of undergraduate physics labs to learning outcomes was recently investigated by Natasha G. Holmes and Carl E. Wieman . This detailed and comprehensive study was carried out on different physics undergraduate lab courses, over multiple institutes in the U.S., involving multiple instructors and more than 3,000 students.…”
Section: Introduction: the Goals And Challenges Of Undergraduate Labsmentioning
confidence: 99%
“…To understand the reasons behind the lack of benefits, the authors probed further and discovered that the causes could be found in the “structured” or “content‐based” labs . As the authors explain: “The only thinking that the students said they did in the structured lab and content focussed labs was in analysing data and checking if it was feasible to finish the lab in time.…”
Section: Introduction: the Goals And Challenges Of Undergraduate Labsmentioning
confidence: 99%
“…In particular, our final lab course aims to teach students how to develop research goals, define criteria, and assess feasibility. A student design approach provides the best opportunity for accomplishing each of these goals [3,4], but effective methods for student designed labs have not been fully explored. We discuss a novel approach to student designed labs aimed at helping students develop their ideas and make plans before the execution phase of a project while providing students a more authentic view of experimental research.…”
Section: Introductionmentioning
confidence: 99%